OPTIMIZING CONFISCATION OF CORRUPTION ASSETS THROUGH CIVIL LAW - Zefanya Gloria Tachika Lianta; Amelia Chandra Kartika; Naya Hapsari; Tiara Tiara; Arneta Adelia Santoso; Marcelina Lovely Awaeh (President University, 2022)
For a long time, Indonesia has been facing the complexity of corruption cases. Corruption turns out to be more than just a legal issue. It is also a violation of people's economic and social rights. Poverty, significant social disparities, and overall state losses are also the result of corruption, so Indonesia must always find solutions to rampant corruption. The Follow the Money approach is one of the approaches used in Indonesia to combat corruption today. This approach also uses the main concept of the Corruption Eradication Law (UU PTPK), namely the concept of